2016
DOI: 10.18632/oncotarget.12468
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of HLA-DRB1 and its clinical significance in psoriasis

Abstract: Increasing evidences indicate that the abnormal DNA methylation is involved in the pathogenesis of psoriasis. A number of SNPs in HLA-DRB1 have been found being associated with the risk of psoriasis, however it is unclear that metylation status within HLA-DRB1 in psoriasis. Here, DNA and RNA were obtained from epidermis of 56 patients with plaque psoriasis and 28 healthy volunteers served as the control group. For the first time, we discovered mean methylation rate for HLA-DRB1 is 52.2%, 64.3% and 68.1% in epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Zong et al . [ 48 ] demonstrated that HLA-DRB1 methylation in psoriatic lesions is significantly lower than in psoriatic nonlesions and is negatively correlated to PASI score; thus, hypomethylation of HLA-DRB1 is associated with the severity of psoriasis. Chen et al .…”
Section: H Omocysteine Dna M Ethylatiomentioning
confidence: 99%
“…Zong et al . [ 48 ] demonstrated that HLA-DRB1 methylation in psoriatic lesions is significantly lower than in psoriatic nonlesions and is negatively correlated to PASI score; thus, hypomethylation of HLA-DRB1 is associated with the severity of psoriasis. Chen et al .…”
Section: H Omocysteine Dna M Ethylatiomentioning
confidence: 99%
“…There is increasing evidence that the lower methylation (hypomethylation) of HLA-DRB1 gene promoter, leading to HLA-DRB1 overexpression, is associated with a higher risk of developing various autoimmune diseases. The loss of DNA methylation has been shown to be involved in psoriasis and multiple sclerosis pathogenesis [118,119]. Consistently, the rs9267649 protective variant was associated with increased DNA methylation and lower HLA-DRB1 expression in multiple sclerosis [119].…”
Section: Significance Of Hla-drb1 Methylation Statusmentioning
confidence: 72%
“…As expected, the differentially methylated genes identified in the skin are mostly associated with epidermal and keratinocyte differentiation, and cellular regeneration [39, 7476]. Four skin biopsy-based studies identified members of the S100A family, part of the epidermal differentiation complex, as top differentially methylated hits [39, 40, 7578]. Many studies have failed to identify differences in skin biopsies in affected non-inflamed skin compared to healthy controls [39, 75, 76].…”
Section: Dna Methylation Studies In As Ibd and Psoriasismentioning
confidence: 74%
“…Unfortunately, this was the only study to incorporate both genetic and DNA methylation analysis, and thus, for most psoriasis-associated loci, there is no information as to whether genetic variants operate through methylation to influence disease. The few single-gene studies have identified differential methylation in the promoter regions of p15 , p16 , p21 , ID4 , IFNG and HLA-C [69, 72, 77, 78, 80]. All had associated changes in gene expression.…”
Section: Dna Methylation Studies In As Ibd and Psoriasismentioning
confidence: 99%